Critical Review of the Evidence on 5-Aminosalicilate for Chemoprevention of Colorectal Cancer in Ulcerative Colitis: A Methodological Question - Margagnoni, Giovanna; Pagnini, Cristiano; Menasci, Francesca; Festa, Stefano; Delle Fave, Gianfranco (Current Clinical Pharmacology, 2014)
Even though the exact amount of the increased risk is not known, patients with Ulcerative Colitis (UC) are more likely to develop colonic malignancy compared with the general population. 5-aminosalicilic acid (5-ASA) compounds are the mainstay therapy for mild-moderate UC, and their use for chemoprevention of colorectal cancer has been proposed, but the evidences are not univocal. Aim of the present work is to critically revise the available data on 5- ASA utilization for cancer chemoprevention, as well as the possible impact in the management of UC patients. In clinical practice, in fact, the best means to measure the dimension of a therapeutic effect is the number needed to treat (NNT). In our study, we show how different basal risk of colorectal cancer reported in studies coming from Europe and USA can affect the NNT, making the strategy “cost-effective” or not. Since prospective randomized controlled trials to address the chemopreventive effect of 5-ASA are not feasible, evidence relays upon observational studies that may imply several biases. Therefore, the heterogeneity of the data is mainly consequent to the different methodological approach of the published studies, in terms of study design, data collection, definitions of regular use of medication and measures of therapeutic efficacy. In addition, two meta-analyses are available with apparently conflicting results. Nonetheless, 5-ASA represents an ideal chemopreventive agent for its anti-inflammatory property, safety, acceptability and inexpensiveness, and even ECCO guidelines recommend 5-ASA long term use, as these compounds may decrease the incidence of CRC.
Keywords: chemoprevention